Badanie znajomości dyferencyjnego słownictwa gwarowego wśród mieszkańców wsi – propozycje metodologiczne .......... 659 - Piechnik, Anna (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
RESEARCHING THE KNOWLEDGE OF DIFFERENTIAL DIALECTAL VOCABULARY AMONG RURAL RESIDENTS. METHODOLOGICAL PROPOSALS The article presents an original questionnaire-based method for researching the knowledge of dialectal vocabulary among rural residents. The study is carried out in several stages. The first stage should be conducted among students of the upper grades (7–8) of elementary school, since they are the oldest students who receive education within their native environment. The survey should take place at school in order to avoid the influence of representatives of older generations on the responses. Each student’s questionnaire should be assigned a unique code, and then students should be asked to complete an identical questionnaire marked with the same, but based on the responses from older individuals (grandparents, neighbors, possibly parents) with whom they have frequent, daily contact. This method of vocabulary collection makes it possible to observe similarities and differences in the lexical resources across generations, and to assess the knowledge of new vocabulary by the middle generation, as well as of differential dialectal vocabulary by the youngest generation. From theis lexicon, the researcher ought to: 1) select words which are only present in the responses of the oldest participants, and then use a separate test to assess the declared active and passive knowledge of these words among students, as well as their understanding of the meaning of those words; and 2) select words which appear exclusively in student responses and use a separate test to assess their knowledge among the representatives of the oldest generation. This method proved effective in a study of personal expressivisms referring to children in communities within the foothill dialectal area.